Health Professionals Prefer to Communicate Risk-Related Numerical Information Using "1-in-X" Ratios. (April 2018) - Sirota, Miroslav; Juanchich, Marie; Petrova, Dafina; Garcia-Retamero, Rocio; Walasek, Lukasz; Bhatia, Sudeep
Background. Previous research has shown that format effects, such as the "1-in-X" effect—whereby "1-in-X" ratios lead to a higher perceived probability than "N-in-N*X" ratios—alter perceptions of medical probabilities. We do not know, however, how prevalent this effect is in practice; i.e., how often health professionals use the "1-in-X" ratio.Methods. We assembled 4 different sources of evidence, involving experimental work and corpus studies, to examine the use of "1-in-X" and other numerical formats quantifying probability.Results. Our results revealed that the use of the "1-in-X" ratio is prevalent and that health professionals prefer this format compared with other numerical formats (i.e., the "N-in-N*X", %, and decimal formats). In Study 1, UK family physicians preferred to communicate prenatal risk using a "1-in-X" ratio (80.4%, n = 131) across different risk levels and regardless of patients' numeracy levels. In Study 2, a sample from the UK adult population ( n = 203) reported that most GPs (60.6%) preferred to use "1-in-X" ratios compared with other formats. In Study 3, "1-in-X" ratios were the most commonly used format in a set of randomly sampled drug leaflets describing the risk of side effects (100%, n = 94). In Study 4, the "1-in-X" format was the most commonly used numerical expression of medical probabilities or frequencies on the UK's NHS website (45.7%, n = 2, 469 sentences).Conclusions. The prevalent use of "1-in-X" ratios magnifies the chances of increased subjective probability. Further research should establish clinical significance of the "1-in-X" effect.